Culture media-based selection of endothelial cells, pericytes, and perivascular-resident macrophage-like melanocytes from the young mouse vestibular system - Zhang, Jinhui (Hear Res, 2017)
The vestibular blood-labyrinth barrier (BLB) is comprised of perivascular-resident macrophage-like melanocytes (PVM/Ms) and pericytes (PCs), in addition to endothelial cells (ECs) and basement membrane (BM), and bears strong resemblance to the cochlear BLB in the stria vascularis. Over the past few decades, in vitro cell-based models have been widely used in blood-brain barrier (BBB) and blood-retina barrier (BRB) research, and have proved to be powerful tools for studying cell-cell interactions in their respective organs. Study of both the vestibular and strial BLB has been limited by the unavailability of primary culture cells from these barriers. To better understand how barrier component cells interact in the vestibular system to control BLB function, we developed a novel culture medium–based method for obtaining EC, PC, and PVM/M primary cells from tiny explants of the semicircular canal, sacculus, utriculus, and ampullae tissue of young mouse ears at post-natal age 8 - 12 d. Each phenotype is grown in a specific culture medium which selectively supports the phenotype in a mixed population of vestibular cell types. The unwanted phenotypes do not survive passaging. The protocol does not require additional equipment or special enzyme treatment. The harvesting process takes less than 2 h. Primary cell types are generated within 7 - 10 d. The primary culture ECs, PCs, and PVM/M shave consistent phenotypes more than 90% pure after two passages (~ 3 weeks). The highly purified primary cell lines can be used for studying cell-cell interactions, barrier permeability, and angiogenesis.